KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KETERLIBATAN ORANG TUA DALAM PENDIDIKAN ANAK DISEKOLAH SD SWASTA SEJAHTERA - Syahputra, Muhammad Rizki; Zulqaidah, Zulqaidah; Harahap, Hasriyati; Br. Marpaung, Dian Pratiwi; Tanjung, Rama Satya; Nurroyian, Nurroyian (Universitas Islam Negeri Sumatera Utara Medan, 2024)
To create good communication between parents and the institution of course requires good and maintained interaction at school. This study was carried out to find out how important organizational communication is in fostering parental involvement in student education at Sejahtera Private Elementary School, building effective communication channels, encouraging parental participation, and using technology to increase parental involvement. By using this type of field research, this study can be carried out well. The targets that have been researched are Sejahtera Private Elementary Schools. And the subject is one of the teachers who teaches at the school. The methods used to collect data in this research were observation, question and answer, and storage of documentation. After carrying out this research, the results obtained stated that good organizational communication can foster the role of parents in supporting student education at school. The author is aware of the shortcomings in this report and hopes for constructive suggestions from readers for future improvements. It is hoped that the research we conducted will be useful for those of us who read it to interpret the importance of organizational communication in the context of student education.